2019
DOI: 10.1016/j.physbeh.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

3,4-methylenedioxymethamphetamine (MDMA) impairs the extinction and reconsolidation of fear memory in rats

Abstract: Clinical trials have demonstrated that 3,4-methylenedioxymethamphetamine (MDMA) paired with psychotherapy is more effective at reducing symptoms of post-traumatic stress disorder (PTSD) than psychotherapy or pharmacotherapy, alone or in combination. The processes through which MDMA acts to enhance psychotherapy are not well understood. Given that fear memories contribute to PTSD symptomology, MDMA could augment psychotherapy by targeting fear memories. The current studies investigated the effects of a single a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 63 publications
2
34
0
2
Order By: Relevance
“…The substituted amphetamine 3,4-methylenedioxymethamphetamine (MDMA) induces serotonin release by binding primarily to presynaptic serotonin transporters 12 . MDMA has been shown to enhance fear memory extinction, modulate fear memory reconsolidation (possibly through an oxytocin-dependent mechanism), and bolster social behavior in animal models 13 , 14 . Pooled analysis of six phase 2 trials of MDMA-assisted therapy for PTSD have now shown promising safety and efficacy findings 15 .…”
Section: Mainmentioning
confidence: 99%
“…The substituted amphetamine 3,4-methylenedioxymethamphetamine (MDMA) induces serotonin release by binding primarily to presynaptic serotonin transporters 12 . MDMA has been shown to enhance fear memory extinction, modulate fear memory reconsolidation (possibly through an oxytocin-dependent mechanism), and bolster social behavior in animal models 13 , 14 . Pooled analysis of six phase 2 trials of MDMA-assisted therapy for PTSD have now shown promising safety and efficacy findings 15 .…”
Section: Mainmentioning
confidence: 99%
“…The other main interesting feature of S1R is its modulatory action over chromatin remodeling complexes, which lead to a rearrangement of gene expression (Demmerle et al, 2012;Tsai et al, 2015). Therefore, the positive outcomes on traumarelated fear-memory extinction and memory reconsolidation elicited by compounds such as ayahuasca and MDMA might result from the activation of this receptor (Feduccia and Mithoefer, 2018;Inserra, 2018;Hake et al, 2019).…”
Section: E S1 Receptormentioning
confidence: 99%
“…MDMA may also modify the sensitivity to social reward in mice, an effect lasting weeks after a single dose (Nardou et al, 2019), reminiscent of the "integration therapy" process after an MDMA experience, wherein a patient is encouraged to consider how emotional shifts in the aftermath of their MDMA session may be integrated into daily life (Greer and Tolbert, 1986). Finally, MDMA disrupts fear memories in a widely used model for PTSD (Young et al, 2015(Young et al, , 2017Hake et al, 2019), wherein a conditioned fear memory is extinguished by re-cueing the memory in a safe context.…”
Section: Clinical Perspectives Of Ketaminementioning
confidence: 99%